DIGITAL TRANSFORMATION OF ISLAMIC RELIGIOUS EDUCATION LEARNING IN ELEMENTARY SCHOOLS: A CASE STUDY FROM INDONESIA - Haris, Mohammad Akmal (Sekolah Tinggi Agama Islam Al Hidayah, 2026)
This study analyzes the changes in teaching Islamic Religious Education at UPTD SD Negeri 1 Tanjungkerta during the digitalization process. This study specifically analyzes the role of digital technology in teaching Islamic Religious Education, in addition to the challenges and supporting factors related to its use. The method used is a qualitative approach with semi-structured interviews and classroom observations of two Islamic Religious Education teacher who is experienced in the use of digital technology. The results show that digital technologies, such as YouTube and digital presentations, have a positive impact on visualizing complex material such as Islamic history and worship, as well as improving student understanding and participation. However, the main challenges faced are limited devices, lack of formal training for teachers, and unstable internet connection problems. Support from the Principal and the teacher-to-teacher learning community is the main supporting factor in the adoption of technology. In addition, technology-based learning can improve flexibility, interactivity, and learning quality, but it requires the continuous development of digital competencies in order to be implemented optimally. His study contributes to understanding digital pedagogical adaptation in Islamic education at the primary school level and provides insights for future learning practice development.